Towards quantum information with trapped ions at NIST - Leibfried, D; DeMarco, B; Meyer, V; Rowe, M; Ben-Kish, A; Barrett, M; Britton, J; Hughes, J; Itano, WM; Jelenkovic, B; Langer, C; Lucas, D; et al. (2003)
We report experiments on coherent quantum-state synthesis and the control of trapped atomic ions. This work has the overall goal of performing large-scale quantum information processing; however, such techniques can also be applied to fundamental tests and demonstrations of quantum mechanical principles, as well as to the improvement of quantum-limited measurements.